Three-dimensional mapping of distal humerus fracture - Chao Wang; Yong Zhu; Haitao Long; Zhangyuan Lin; Ruibo Zhao; Buhua Sun; Shushan Zhao; Liang Cheng (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Distal humerus fractures (DHFs) constitute one-third of elbow fractures approximately. In this study, we aim to define and analyze the fracture lines and morphological features of DHFs using mapping technique. Methods One hundred and two DHFs were retrospectively reviewed. All the computed tomography (CT) data were used to manually reconstruct and virtually reduce the DHF fragments to fit a standard 3D model. Smooth curves were depicted accurately onto the surface of the template to represent the fracture lines. All the curves were overlapped onto the model to create the 3D fracture map and heat map. Results Our analysis was based on 102 CT images of DHFs, contributed by 59 male and 43 female patients (mean age, 46 years; range, 18-93 years), and included 15 type A, 25 type B, and 62 type C fractures. On mapping, the hot zones were located in the radial fossa, coronoid fossa, olecranon fossa, and the external part of the trochlear. Conversely, the cold zones were noted in medial condyle, the medial side of the trochlear, and the anterolateral area on the supracondylar ridge. Conclusions Our study firstly shows the fracture lines and morphological features of distal humeral fractures by three-dimensional mapping technology. Distal humerus fracture lines are characteristic and highly related to the micro-architecture difference of distal humerus, which may provide some guidance for the treatment plan selection and surgical fixation design.